A methodological approach to the determination of optimal parameters of district heating systems with several heat sources. (15th October 2019) - Stennikov, Valery A.; Barakhtenko, Evgeny A.; Sokolov, Dmitry V.
Abstract: The determination of optimal parameters is of great importance to ensure the operability of a district heating system. Solving this problem entails providing the necessary network transmission capacity by determining pipe diameters, sites and parameters of pumping stations. The Melentiev Energy Systems Institute of Siberian Branch of the Russian Academy of Sciences has proposed methods to solve problem. A significant feature of these methods lies in that they make it possible to use complex mathematical models of the equipment used and flexibly adjust the computational procedure to the specific features of the system to be modelled. Normally, district heating systems have several heat sources. The practical problems for such systems have been solved by a technique based on the decomposition of the model of a district heating system according to heat source service areas. The decomposition breaks the unity of the computational process. As a result, the solution obtained is not optimal for the original district heating system model. The paper presents a methodological approach to determining optimal parameters of district heating systems with several heat sources. The approach employs a modified dynamic programming optimization method that provides an optimal solution without decomposition into the heat source service areas. Highlights: Optimization of district heating system parameters is considered. A modified dynamic programming optimization method is developed. A methodological approach and algorithms are presented. The approach is applied to district heating systems with several heat sources. The approach has been demonstrated on a real district heating system.